CULTURAL FEATURES OF FITZGERALD’S WORKS - Bekmurodova E’zoza (TADQIQOTLAR, 2025)
Annotation: This article explores the cultural features embedded in F. Scott Fitzgerald’s works, focusing on his portrayal of 20th-century American society, themes of the American Dream, and the cultural identity of the Jazz Age. Through an analysis of key texts, including The Great Gatsby, the study highlights Fitzgerald’s unique ability to reflect the societal values, challenges, and contradictions of his time.